LIM Domain-Containing Protein Trip6 Can Act as a Coactivator for the v-Rel Transcription Factor - Koedood Zhao, Marieke (Gene Expr, 2018)
The retroviral oncoprotein v-Rel is a transcriptional activator in the Rel/NF-κB family of eukaryotic transcription factors. v-Rel malignantly transforms a variety of cell types in vitro and in vivo, and its transforming activity is dependent on the ability of v-Rel to bind to DNA and activate transcription. In this report, we used the yeast two-hybrid assay to identify proteins that interact with C-terminal sequences of v-Rel that are needed for transcriptional activation and transformation. One protein, Trip6, that we identified in this screen was previously identified as a thyroid hormone receptor-interacting protein. Trip6 is a member of a subfamily of LIM domain-containing proteins that are thought to transport intracellular signals from the cell surface to the nucleus. By several criteria, we show that sequences from Trip6, which include the LIM domains, behave as a coactivator for transcriptional activation by v-Rel. That is, a GAL4-Trip6 fusion protein can activate transcription in yeast and chicken cells, Trip6 can enable C-terminal sequences of v-Rel to activate transcription in yeast, and Trip6 can enhance activation by v-Rel from a κB site reporter plasmid in yeast. Although full-length Trip6 localizes to adhesion plaques, deletion of N-terminal sequences allows human Trip6 to enter the nucleus of chicken cells. Lastly, Northern blotting shows that Trip6 mRNA is expressed in many human tissues. Coexpression of Trip6 does not affect the transforming activity of v-Rel. Taken together, our results indicate that Trip6 may be a protein that is important for the ability of v-Rel to activate transcription and transform cells, and may represent a potential target for blocking Rel-mediated oncogenesis and transcriptional activation.